On the estimation of relative risk from vital statistical data. Issue 2 (June 1979) - Beral, V; Chilvers, C; Fraser, P
Abstract : A method is described for the determination of a measure of relative risk from vital statistical data. If the frequency of disease in a population is linearly related to the level of exposure to a given factor, then a measure of the relative risk can be estimated from the slope and intercept of the regression line. For example, when the exposure is measured in terms of the proportion of the population exposed to the factor, then the relative risk is equal to (Formula: see text). This offers an indirect but simple and inexpensive method for estimating relative risk. It should be used with caution, particularly where confounding factors may be responsible for the apparent association between disease and factor. Applications of the method to estimate the relative risk of (a) circulatory diseases in women using oral contraceptives and (b) ovarian cancer in women with different average family sizes, both yielded relative risk estimates comparable with those obtained from case-control and prospective studies.